Characteristics of electronic cigarette and vape users in Malaysia: Lessons from decision tree analysis - Kartiwi, Mira; Nik Mohamed, Mohamad Haniki; Ab Rahman, Jamalludin; Draman, Samsul; Ab Rahman, Norny Syafinaz (Organization of Pharmaceutical Unity with BioAllied Sciences (OPUBS), 2020)
Introduction: The use of electronic cigarette and vape (ECV) among adults has been rapidly in Malaysia. Objectives: The primary objective of this paper is to understand the characteristics of ECV users in Malaysia by assessing the perceptions and demographic variables. The influence of perceptions and demographic variables were assessed on the current status of ECV use. Several predictor variables included in this study were: seven demographics variables (i.e., age, gender, race, residence, marital, occupation and education) and twenty variables on the perception of ECV use. An Induction Decision Tree (ID3) algorithm, one of the renowned data mining technique, was used in this study. Materials and Methods: A number of simulations was carried out on the dataset which was extracted from the National Electronic Cigarette Survey (NECS) 2016. Results: The result of this study shows that the most critical variable identified in this study was gender, hence indicates decision for ECV uses significantly differs among male and female. Conclusion: The findings of this study would contribute towards strategizing public health campaign on smoking cessation.